Structural study of liquid rare earth metals from charged hard sphere reference fluid - Thakor, P.B.; Gajjar, P.N.; Jani, A.R. (Condensed Matter Physics, 2002)
The present article deals with the investigation of structure factor, s(q) ; radial distribution function, g(r) and interatomic distance, r₁ of liquid rare earth metals, Nd, Dy, Ho, Er and Lu by adopting Charged Hard Sphere (CHS) reference fluid. To describe electron-ion interaction, our well established model potential along with the dielectric function due to Taylor is used. Good agreement between present and experimental findings is concluded.